2022
DOI: 10.1111/ctr.14644
|View full text |Cite
|
Sign up to set email alerts
|

Which preoperative assessment modalities best identify patients who are suitable for enhanced recovery after liver transplantation? A systematic review of the literature and expert panel recommendations

Abstract: Background: To implement Enhanced Recovery After Surgery (ERAS) protocols for liver transplant (LT) candidates, it is essential to identify tools that can help risk stratify patients by their risk of early adverse post-LT outcomes. Objective:We aimed to identify pre-LT tools that assess functional capacity, frailty, and muscle mass that can best risk stratify patients by their risk of adverse post-LT outcomes. Methods:We first conducted a systematic review following PRISMA guidelines, expert panel review and r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…In view of these results, the American Association for the Study of Liver Diseases guidance document suggests that all cirrhotic patients should be assessed for sarcopenia and frailty with standardized tools both at baseline and longitudinally[ 17 ]. These recommendations are consistent with the implementation of specific protocols such as “enhanced recovery after surgery” protocols to improve recovery after surgery, especially for LT candidates[ 49 ].…”
Section: Why Is It Important To Consider the Muscle In A Liver Transp...supporting
confidence: 57%
“…In view of these results, the American Association for the Study of Liver Diseases guidance document suggests that all cirrhotic patients should be assessed for sarcopenia and frailty with standardized tools both at baseline and longitudinally[ 17 ]. These recommendations are consistent with the implementation of specific protocols such as “enhanced recovery after surgery” protocols to improve recovery after surgery, especially for LT candidates[ 49 ].…”
Section: Why Is It Important To Consider the Muscle In A Liver Transp...supporting
confidence: 57%
“…Achieving the aim of improving pre-transplant fitness within a structured pre-habilitation program, tailored to this patient population as is already recommended by several societies, will be essential to maintain high post-transplant success rates ( 26 , 31 ). Crespo et al identified 4 assessment tools to detect patients suitable for Enhanced Recovery After Surgery (ERAS) protocols in the pre-transplantation period [Karnofsky performance status (KPS), LFI, abdominal muscle mass, cardiopulmonary exercise testing] ( 32 ). A recent systematic review on prehabilitation in patients awaiting LT did not detect an impact on adverse clinical outcomes including mortality due to sparse data ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The goal of anesthesia management for early extubation focuses around maintaining good postoperative analgesia with minimal respiratory depression. Several authors have recommended enhanced recovery pathways for liver transplantation utilizing various strategies to manage pain and aid with recovery in the perioperative period [43][44][45][46]. Most of the initial studies on early extubation utilized a balanced anesthetic approach, with volatile anesthetics supplemented with short acting narcotics such as fentanyl or remifentanil [17][18][19][20]23,35,47].…”
Section: Anesthetic Managementmentioning
confidence: 99%